2015
DOI: 10.1259/bjr.20140477
|View full text |Cite
|
Sign up to set email alerts
|

iPad-based primary 2D reading of CT angiography examinations of patients with suspected acute gastrointestinal bleeding: preliminary experience

Abstract: Tablet computers are emerging as promising devices for mobile visualization of medical images from crosssectional modalities (such as CT and MRI), owing to their good screen resolution, larger display size than that of conventional smartphones and excellent power-to-weight ratio. 1 Among them, the iPad (Apple Inc., Cupertino, CA) has gained wide popularity in the medical community owing to its high screen resolution (.3 MP, i.e. comparable to regular radiological workstations), its reasonably fast processor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Some factors are hardly surprising, such as the time of day, the experience of the radiologist and the number of interruptions À others more puzzling, such as the size and luminescence of the screen, the use of key images in reporting, and the image order in the hanging protocol. (12)(13)(14)(15)(16)(17)(18) Given this complexity, it does not seem unreasonable to assume that the reading times when using AI can be differently affected in a clinical environment and a research environment. This seems supported by studies which find that CAD findings affect the reading times of individual radiologists differently.…”
Section: Introductionmentioning
confidence: 99%
“…Some factors are hardly surprising, such as the time of day, the experience of the radiologist and the number of interruptions À others more puzzling, such as the size and luminescence of the screen, the use of key images in reporting, and the image order in the hanging protocol. (12)(13)(14)(15)(16)(17)(18) Given this complexity, it does not seem unreasonable to assume that the reading times when using AI can be differently affected in a clinical environment and a research environment. This seems supported by studies which find that CAD findings affect the reading times of individual radiologists differently.…”
Section: Introductionmentioning
confidence: 99%
“…In the era of mobile Internet (WIFI or 3G as fundamental carrier), with increasingly large amounts of SMI data of high quality, people desire to rapidly view and process this 3D visualized reconstruction of high quality in a diversified network environment via different client devices without installing special software [ 3 ]. In particular, many studies have reported that there were no significant differences of diagnostic accuracy regarding more and more diseases between mobile devices and the traditional workstations that promoted the further development of medical imaging technology on mobile Internet [ 4 – 9 ]. Presently, the 3D visualized reconstruction techniques in medicine have fallen into the following two main categories: surface rendering and volume rendering [ 10 ], both with their own characteristics to adapt to the Internet application.…”
Section: Introductionmentioning
confidence: 99%
“…Several prior studies have compared image reading apps on mobile devices to standard clinical workstations and found no significant difference in interpretation accuracy for the identification of pulmonary embolism [6,7], acute gastrointestinal bleed on CT angiography [8], acute aortic syndrome [9], cerebral infarction or hemorrhage [7,10,11], and spinal emergencies [12]. However, coronary CTA exams present special challenges for remote interpretation given the small size of coronary arteries (generally <5 mm) and the importance of interactive manipulation of the imaging volume into reformatted planes, as opposed to the standard axial, sagittal, and coronal planes.…”
Section: Introductionmentioning
confidence: 99%